#### Answer

m=1

#### Work Step by Step

m=$\frac{y_2-y_1}{x_2-x_1}$
m=$\frac{-5-(-6)}{6-5}$
m=$\frac{-5+6}{1}$
m=$\frac{1}{1}$
m=1

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

m=1

m=$\frac{y_2-y_1}{x_2-x_1}$
m=$\frac{-5-(-6)}{6-5}$
m=$\frac{-5+6}{1}$
m=$\frac{1}{1}$
m=1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.